Implementasi Metode Artikulasi Melalui Pengenalan Huruf Vocal pada Anak Berkebutuhan Khusus Speech Delay di PAUD Universal Agape Kids Wonosobo Tahun Ajaran 2023/2024 - Dawamatussilmi, Vina; Khoiri , Ahmad; Sugiyanto , Bambang (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
The outcomes of with a field research design, this findings study use a qualitative research methodology. The data sources are gathered from primary and secondary data sources (educational and guidance books for children with special needs, references related to children with special needs speech delay, articulation methods, previous thesis, articles, journals, and internet sites), while the data collection technique uses interview, observation, and documentation methods. Furthermore, data sources were procured from the research participants, which included principals, educators, and students of PAUD Universal Agape Kids, a program serving ten children in the 2–4-year age range. An analysis of the data obtained is followed by the development of a particular relationship pattern or hypothesis based on the hypothesis formulated based on the data, and finally, the data is repeatedly searched to determine whether the hypothesis can be accepted or rejected based on the data collected. This type of data analysis is known as an inductive qualitative data analysis technique. If it turns out that the hypothesis is correct and is supported by evidence that can be repeatedly obtained using the tringulation procedure, it becomes a theory. The results of the study show that: 1) the learning process at PAUD Universal Agape Kids Wonosobo aims to help develop children's mindset in learning articulation therapy, with articulation therapy children can develop conversational skills so that they can improve their speaking skills and be able to express language according to their age. 2) the inhibiting factors in the implementation of the articulation method through the introduction of vocal letters in children with special needs speech delay are speech disorders caused by damage to the oral structure, the appearance of a lack of confidence caused by children experiencing speech delays, lack of stimulation from an early age, lack of parental understanding of speech delay children, lack of socialization with the surrounding environment, children feeling insecure with their peers, As for the supporting factors in the implementation of the articulation method through letter recognition in children with special needs speech delay, namely children who have special needs in Agpe Kids universal PAUD have a great enthusiasm for learning, educators who are serious in learning activities and the seriousness of teachers in teaching, teachers or educators can facilitate the needs of students. 3) the implementation of the articulation method through the introduction of vocal letters in children with special needs speech delay, namely early childhood education in children who have special needs, especially in speech disorders, it is very important for educators to introduce vocal letters as an introduction to their pronunciation, especially children who have speech impairments the articulation method can be used as the main support for their needs, With this media, children will know how to see and hear the vibrations of letters.